Dr. Multicast: Rx for data center communication scalability - Vigfusson, Ymir; Abu-Libdeh, Hussam; Balakrishnan, Mahesh; Birman, Ken; Tock, Yoav (LADIS '08: Proceedings of the 2nd Workshop on Large-Scale Distributed Systems and Middleware, 2008)
Data centers avoid IP Multicast (IPMC) because of a series of problems with the technology. We introduce Dr. Multicast (MCMD), a system that maps IPMC operations to a combination of point-to-point unicast and traditional IPMC transmissions. MCMD optimizes the use of IPMC addresses within a data center, while simultaneously respecting an administrator-specified acceptable-use policy. We argue that with the resulting range of options, IPMC no longer represents a threat and can therefore be used much more widely.